An Evaluation of the Beyond High School Model on the Self- Determination of Students With Intellectual Disability - Susan B. Palmer; Michael L. Wehmeyer; Karrie A. Shogren; Kendra L. Williams-Diehm; Jane H. Soukup (Career Development and Transition for Exceptional Individuals, 2012)
Students with intellectual disability are often served in community-based services to promote effective adult outcomes in employment, community inclusion, and independent living (Gaumer, Morningstar & Clark (2004). Beyond High School (Wehmeyer, Garner, Lawrence, Yeager, & Davis, 2006), a multi-stage model to promote student involvement in educational planning, was effectively used by 109 students with mild and moderate levels of intellectual disability between 17.8 and 21 years of age to increase student abilities. Results are discussed in regard to improved transition opportunities for individuals with intellectual disability such as those afforded through post-secondary education.
Keywords: intellectual disability; postschool outcomes; self-determination